A molecular photosensitizer achieves a V oc of 1.24 V enabling highly efficient and stable dye-sensitized solar cells with copper(II/I)-based electrolyte - Dan Zhang (Nature Portfolio, 2021)
Designing photo-sensitisers with high open-circuit voltage (V oc) is desirable to enhance the power conversion efficiency (PCE) of co-sensitized solar cells. Here, the authors employ a judiciously tailored organic sensitiser MS5 with copper electrolyte to achieve a V oc of 1.24 V, and recorded PCE of 34.5% under ambient light.